THE IMPLEMENTATION OF SNOWBALL THROWING METHODE TO INCREASE THE COLLEGE CREDIT AT THE BALANCE CONCEPT IN ENGINEERING MECHANICS SUBJECT - Tarita Aprilani Sitinjak (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
The increase of study achievement is one of the purposes of lesson process in university. Academically, this research has goal to learn the implementation of Snowball Throwing models tend to increasecollege achievement at the balance concept in Engineering Mechanics subject at Education of Building Engineering Departement Palangka Raya University. To achieve the research goal, the research was held in a year. The data collected by doing interview, spread the brochure, observation, test and field note. The parameter of this research is college credit achievement at the balance concept in Engineering Mechanics subject using Snowball Throwing lesson model. The result of this research showsthat there is significant increase of college achievement at second cycle. First cycle the past progress is 55 %,with the average point 60,95 and 11 college of 20 college has past, meanwhile in second cycle increasing significantly, the average point became 79,5, which means the past progressis 95%, in second cycle only one student fail.Furthermore, in lesson process there is also increasing number from 2 (sufficient) become 3,5 (good).